Development of a Virtual Environment for the Simulation of Electrical Maneuvers in Substations: A Case Study - Riveros Hernández, David Antonio; Nausan García, Diego Hernando; García Miranda, Diana Stella; Palacios Osma, José Ignacio (Ingeniería Solidaria, 2017)
Introduction: This is the result of a research project that intends to show the importance of including the electrical substation simulator in the course that bears the same name (School of Engineering, Universidad Distrital Francisco José de Caldas). We propose an improved version of the simulator that includes all existing configurations and design modules. Method: Sample surveys were used to find out the students’ perception of the electric substation simulator as a learning methodology and its effect on course repetition figures. A summary of how the software was developed and its validation through a simulation that allows to show the advantages of its use for electrical maneuvers, along with recent modifications, is provided. Results: The potentiality of the tool is shown by the simulation of an electric maneuver. Through the sample surveys, it was obtained that more than 80 % of the students affirm that the simulator was a useful tool for electrical maneuvers, since this topic was very difficult to learn; therefore, it can contribute to reduce course repetition rates. Conclusions: The inclusion of the simulator demonstrated the usefulness of this virtual tool for understanding the operation and maintenance of high and extra high voltage installations (electrical substations). This is framed by the concept of virtual laboratories and is valid for the training of science and engineering students, thus contributing to improve their performance in different subjects.